Cement composition and method for producing the cement composition

A cement composition with controlled proportions of cement clinker, gypsum, coal ash, and limestone, along with a hardening accelerator, addresses DEF in high-temperature regions by suppressing expansion and maintaining strength while reducing emissions.

JP7604110B2Active Publication Date: 2024-12-23MITSUBISHI UBE CEMENT CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020064850
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-31
Publication Date
2024-12-23
Estimated Expiration
2040-03-31

AI Technical Summary

Technical Problem

In high-temperature regions, delayed ettringite formation (DEF) in cement compositions leads to structural deterioration due to temperature increases during curing, which existing methods fail to adequately address, particularly when using coal ash as a mixture, and limestone promotes DEF while reducing cement clinker content for environmental benefits.

Method used

A cement composition comprising specific proportions of cement clinker, gypsum, coal ash, and limestone, with controlled Blaine specific surface areas and particle sizes, along with a hardening accelerator, to suppress DEF and maintain compressive strength.

Benefits of technology

The composition effectively reduces DEF expansion, lowers CO2 emissions, and ensures sufficient compressive strength development, making it suitable for high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007604110000001
    Figure 0007604110000001
  • Figure 0007604110000002
    Figure 0007604110000002
  • Figure 0007604110000003
    Figure 0007604110000003
Patent Text Reader

Abstract

To provide a cement composition which can be produced with more reduction of the amount of CO2 emission than before, suppresses expansion with DEF, and has sufficient compressive strength development.SOLUTION: Provided is a cement composition containing cement clinker in which the amount of C3A calculated by Bogue's formula is 8.0-14.0 mass%, gypsum, and an admixture including coal ash and limestone. The blaine specific surface area of the coal ash is 3900-10000 cm2 / g, the content of the admixture, assuming that the total content of the cement clinker, the gypsum and the admixture is 100 mass%, is 5.0-32.5 mass%, the content of the coal ash is 2.5-30.0 mass%, and the content of the limestone is 2.5-24.0 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to cement compositions and methods for making cement compositions. [Background technology]

[0002] In high-temperature regions overseas, the occurrence of delayed ettringite formation (DEF), which is caused by the rise in temperature during the hardening of cement compositions, is a problem. DEF refers to the following phenomenon of ettringite regeneration. First, the initial high-temperature curing and heat generation from the cement composition cause the temperature inside the concrete to rise significantly, causing ettringite (3CaO·Al 2 O 3 3CaSO 4 32H 2 O) decomposes. Then, when moisture is supplied to the concrete while it is in service, ettringite reforms. The reformation of ettringite causes expansion of the hardened body structure, which leads to serious deterioration of the concrete, such as cracks.

[0003] In order to reduce DEF, for example, the SO in the cement composition, which is the raw material for ettringite formation, is used to densify the hardened body structure and suppress the supply of moisture to the inside of the hardened body when the concrete is in service, thereby suppressing the regeneration of ettringite. 3 It is believed that methods such as reducing the content of ethyl alcohol and lowering the maximum temperature reached by the heat generated by the hardening of the cement composition (suppressing the adiabatic temperature rise) to suppress the decomposition of ettringite are effective.

[0004] In high-temperature regions, coal ash is often mixed into cement (a mixture of cement clinker and gypsum) to improve fluidity and durability. By replacing part of the cement with coal ash, the SO 3The content of coal ash is reduced and the hardened body structure is densified, and the effect of suppressing DEF is expected. However, when the amount of coal ash added to the cement composition is about 10 mass%, the effect of suppressing the expansion of the hardened cement body associated with the regeneration of ettringite is not sufficient (for example, Non-Patent Document 1). On the other hand, when the amount of coal ash added to the cement composition is 25 mass% or more, it has been reported that the expansion of the hardened cement body can be suppressed even under conditions where DEF is likely to occur (for example, Non-Patent Document 2). In other words, the blending of coal ash is effective from the viewpoint of suppressing DEF itself or suppressing the expansion of the hardened cement body associated with DEF. However, when the content of coal ash in the cement composition is increased, a problem such as low strength development as a cement composition may generally occur.

[0005] Cement clinker, the raw material for cement, emits CO during its manufacturing process. 2 It is known that CO emissions are high. From the viewpoint of preventing global warming, it is desirable to further increase the content of admixtures such as coal ash in the cement composition in the future in order to reduce the content of cement clinker. In addition to coal ash, limestone, for example, is also known as an admixture. In high-temperature regions overseas, cement compositions containing limestone as an admixture are used as Portland limestone cement. 2 From the viewpoint of reducing emissions, the addition of limestone is effective, but it has been reported that the addition of limestone promotes DEF (e.g., Non-Patent Document 2). [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Takanori Ikeda et al., "Effect of Admixtures on the Inhibition of DEF Expansion of Mortar Cured at High Temperatures," Proceedings of the Japan Concrete Institute, 2008, Vol. 30, No. 1, p. 135-140 [Non-Patent Document 2] Shingo Asamoto et al., "Study on the effect of carbonate ions on delayed ettringite formation", Proceedings of the Japan Concrete Institute, 2016, Vol. 28, No. 1, pp. 819-824 [Non-Patent Document 3] Eiji Marutani et al., "Development of a quality control method for cement using adiabatic calorimeter for small samples", Proceedings of the Cement and Concrete Society, 2007, Vol. 61, No. 1, pp. 86-91 [Non-Patent Document 4] "Guidelines for Crack Control in Mass Concrete 2016", 2016, Japan Concrete Institute Summary of the Invention [Problem to be solved by the invention]

[0007] In laboratory tests to evaluate the occurrence of DEF in hardened cement bodies such as concrete, heat is often applied from the outside to induce DEF, and pre-curing is often performed at 80°C or higher. However, when considering actual mass concrete prepared outdoors, it is thought that the heat generated by the hardening of the cement composition may accumulate in the hardened cement body and induce DEF. Therefore, in order to further reduce the risk of DEF, it is desirable to suppress the temperature rise of the cement composition under adiabatic conditions.

[0008] This disclosure relates to 2 The object of the present invention is to provide a cement composition that can be produced with reduced emissions compared to conventional methods, in which expansion associated with DEF is suppressed, and which has sufficient compressive strength development, and a method for producing the same. [Means for solving the problem]

[0009] One aspect of the present disclosure is a C calculated by the Bogue formula. 3 The mixture contains cement clinker having an A content of 8.0 to 14.0 mass%, gypsum, and a mixture containing coal ash and limestone, and the Blaine specific surface area of ​​the coal ash is 3900 to 10000 cm 2 / g, and the total content of the cement clinker, the gypsum, and the admixture is taken as 100 mass%, the content of the admixture is 5.0 to 32.5 mass%, the content of the coal ash is 2.5 to 30.0 mass%, and the content of the limestone is 2.5 to 24.0 mass%.

[0010] The cement composition contains a predetermined amount of admixture containing coal ash having a predetermined Blaine specific surface area and limestone for a predetermined cement clinker, thereby suppressing the expansion of the hardened cement body caused by DEF. In addition, by combining the cement composition with a predetermined cement clinker and setting the content of the admixture to a predetermined amount, the hardened cement body can have sufficient compressive strength while using the admixture.

[0011] The content of the gypsum relative to the total content of the cement clinker, the gypsum and the admixture is 100 mass %, and the content of the gypsum is 3 The gypsum content may be 0.5 to 3.5% by mass in terms of mass. By keeping the gypsum content within the above range, the occurrence of DEF accompanying hardening of the cement composition can be further reduced. Also, by keeping the gypsum content within the above range, the compressive strength of the hardened cement body prepared using the cement composition can be further improved.

[0012] The above cement clinker is calculated by the Bogue formula 3 The amount of S may be 35.0 to 65.0 mass%. 3 By keeping the S content within the above range, the occurrence of DEF accompanying the hardening of the cement composition can be further reduced. 3 By ensuring that the S content is within the above range, the compressive strength of a hardened cement body prepared using the cement composition can be further improved.

[0013] The coal ash may have a 4 μm residue of 40 to 85 vol % and a 32 μm residue of 0 to 20.0 vol %. When the coal ash has the above particle size distribution, the generation of DEF accompanying the hardening of the cement composition can be further reduced. When the coal ash has the above particle size distribution, the compressive strength of the hardened cement body prepared using the cement composition can be further improved. Furthermore, when the coal ash has the above particle size distribution, it is expected that the adiabatic temperature rise accompanying the hardening of the cement composition can be suppressed.

[0014] The cement composition further contains a hardening accelerator, and the content of the hardening accelerator may be 0.1 to 20 parts by mass relative to 100 parts by mass of the total amount of the cement clinker, the gypsum, and the admixture. By containing the hardening accelerator in the cement composition within the above range, the compressive strength of the hardened cement body prepared using the cement composition at an early age can be further improved, and early demolding can be made possible. This allows for appropriate workability.

[0015] One aspect of the present disclosure is a C calculated by the Bogue formula. 3 Cement clinker, gypsum, and blaine having a specific surface area of ​​3900 to 10000 cm 2 The present invention provides a method for producing a cement composition, comprising: a step of mixing coal ash having a molecular weight of 1.5 to 2.5 / g with an admixture containing limestone, in which the cement clinker, the gypsum, the coal ash and the limestone are mixed in such a way that, relative to a total content of the cement clinker, the gypsum and the admixture, the content of the coal ash is 2.5 to 30.0 mass%, the content of the limestone is 2.5 to 24.0 mass%, and the content of the admixture is 5.0 to 32.5 mass%, relative to a total content of the cement clinker, the gypsum, and the admixture, which is 100 mass%.

[0016] The method for producing the cement composition includes mixing a predetermined cement clinker with an admixture containing coal ash and limestone in a predetermined ratio, and thus reducing the amount of CO 2It is possible to produce a cement composition with a lower emission amount than before. In addition, in the method for producing a cement composition, a predetermined amount of coal ash having a predetermined Blaine specific surface area and a mixture containing a predetermined amount of limestone are mixed with a predetermined cement clinker, so that the resulting cement composition can suppress the expansion of the hardened cement body caused by DEF. The cement composition obtained in the above production method can be further combined with a predetermined cement clinker and the content of the mixture is set to a predetermined amount, thereby making it possible to make the compressive strength of the hardened cement body sufficient. Effect of the Invention

[0017] According to the present disclosure, CO 2 It is possible to provide a cement composition that can be produced with reduced emissions compared to conventional methods, that suppresses expansion associated with DEF, and that exhibits sufficient compressive strength development, as well as a production method thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, embodiments of the present disclosure will be described. However, the following embodiments are merely examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents. In the following description, when it is written "X to Y" (X and Y are arbitrary numbers), it means "X or more and Y or less" unless otherwise specified.

[0019] One embodiment of the cement composition has a C calculated by the Bogue formula 3 The cement clinker contains cement clinker with an A content of 8.0 to 14.0 mass%, gypsum, and a specified admixture. The Bogue formula is a formula that is widely used to calculate the content of major minerals in cement clinker from the content ratio of the chemical composition. By using the Bogue formula shown below, the tricalcium silicate (3CaO SiO 2 ,C 3 S), dicalcium silicate (2CaO SiO 2 ,C 2 S), and tricalcium aluminate (3CaO·Al 2O 3 , C 3 It is possible to calculate the content shown by A). In the following formula, "%" means "mass%". The chemical formula represents the content ratio (mass%) of each compound shown by the chemical analysis value according to JIS R 5204 "Fluorescent X-ray Analysis Method for Cement".

[0020] <Bogue formula> C 3 S [%]=(4.07 × CaO [%])-(7.60 × SiO 2 [%])-(6.72 × Al 2 O 3 [%])-(1.43 × Fe 2 O 3 [%])-(2.85 × SO 3 [%]) C 2 S [%]=(2.87 × SiO 2 [%])-(0.754 × C 3 S [%]) C 3 A [%]=(2.65 × Al 2 O 3 [%])-(1.69 × Fe 2 O 3 [%]) C 4 AF [%]=3.04 × Fe 2 O 3 [%]

[0021] By designing the cement clinker so that the amounts of interstitial phases such as C 3 A and C 4 AF increase, it is possible to increase the amount of waste and by-products such as fly ash used as cement clinker raw materials, and a cement composition desirable from the viewpoint of reducing the environmental load can be provided.

[0022] The C 3 A content in the cement clinker has a lower limit value of 8.0 mass% or more, preferably 8.5 mass% or more, more preferably 9.0 mass% or more, still more preferably 9.5 mass% or more, and particularly preferably more than 10.0 mass%. C 3By setting the lower limit of the amount of A within the above range, it is possible to produce a cement composition that uses an increased amount of waste and by-products such as coal ash, which are used as a raw material for cement clinker. 3 The upper limit of the amount of A is 14.0% by mass or less, preferably 13.0% by mass or less, more preferably 12.0% by mass or less, even more preferably 11.0% by mass or less, and particularly preferably less than 10.5% by mass. 3 By setting the upper limit of the amount of A within the above range, ettringite (3CaO·Al 2 O 3 3CaSO 4 32H 2 O) during hardening of the cement composition, and can further reduce the increase in adiabatic temperature rise during hardening of the cement composition, and can further suppress the expansion of the hardened cement body associated with DEF.

[0023] C in cement clinker 3 The amount of S is preferably 35.0 to 65.0% by mass, more preferably 40.0 to 60.0% by mass, further preferably 45.0 to 57.5% by mass, and particularly preferably 47.5 to 54.0% by mass. 3 By setting the lower limit of the S content to 35.0 mass% or more, the early strength of the cement composition upon hardening can be further improved. 3 By ensuring that the upper limit of the S content is 65.0 mass % or less, heat generation during hardening of the cement composition can be further suppressed, and the occurrence of DEF can be further suppressed.

[0024] In this specification, C 3 Amount of A and C 3 The S content refers to a value calculated by the Bogue formula using chemical analysis values ​​of cement clinker measured in accordance with the method described in JIS R 5204 "Method for fluorescent X-ray analysis of cement."

[0025] As the gypsum, for example, gypsum dihydrate, gypsum hemihydrate, anhydrous gypsum, etc. can be used. One type of gypsum may be used alone, or a combination of two or more types may be used. The content of gypsum in the cement composition may be the same as the content of gypsum in general Portland cement. The content of gypsum in the cement composition may be the same as the content of gypsum in SO 3 In terms of conversion, the total content of the cement clinker, the gypsum, and the admixture is taken as 100 mass%, and the content is preferably 0.5 to 3.5 mass%, more preferably 1.0 to 3.0 mass%, and even more preferably 1.0 to 2.5 mass%.

[0026] The admixture contains at least coal ash and limestone. The total content of the admixture in the cement composition is determined by the amount of CO 2 From the viewpoint of low carbonization including reduction in the amount of generated carbon dioxide, a higher amount is desirable, whereas from the viewpoint of improving the physical properties (e.g., compressive strength, etc.) of the hardened cement body, a lower amount is desirable. The content of the admixture in the cement composition is 5.0 to 32.5 mass%, preferably 9.5 to 31.0 mass%, more preferably 14.0 to 30.5 mass%, still more preferably 17.5 to 30.0 mass%, and particularly preferably 20.0 to 30.0 mass%, based on 100 mass% of the total content of the cement clinker, the gypsum, and the admixture.

[0027] The coal ash may be, for example, coal ash discharged from a coal-fired power plant. The above-mentioned mixture may contain other components in addition to coal ash and limestone. For example, ash obtained when coal, which is the main fuel, and biomass fuel derived from wood chips, coconut shells, sewage sludge, etc. are charged and mixed as a power generation boiler fuel in a coal-fired power plant can also be used as the mixture.

[0028] The Blaine specific surface area of ​​coal ash is 3900-10000 cm 2 / g, but preferably 4200 to 8000 cm 2 / g, and more preferably 4500 to 6500 cm 2 / g, and more preferably 5000 to 6000 cm 2 / g, and particularly preferably 5100 to 5500 cm 2 / g. The Blaine specific surface area of ​​coal ash can be adjusted, for example, by classification, crushing, etc. of coal ash. The Blaine specific surface area of ​​coal ash may also be adjusted by mixing coal ashes having different Blaine specific surface areas, or by mixing crushed coal ash with classified coal ash. Examples of the classification method of coal ash include air classification, electrostatic classification, sieve classification, gravity field classification, and centrifugal field classification. Examples of the pulverization method of coal ash include a method using equipment such as a ball mill, a jet mill, a rod mill, and a blade mill.

[0029] In this specification, the term "Blaine specific surface area" refers to a value measured in accordance with the method described in JIS R 5201:2015 "Physical test methods for cement."

[0030] The coal ash preferably has a 4 μm residue of 40 to 85 vol. % and a 32 μm residue of 0 to 20.0 vol. % or less, more preferably has a 4 μm residue of 65 to 80 vol. % and a 32 μm residue of 10.0 vol. % or less, and even more preferably has a 4 μm residue of 70.5 to 77.5 vol. % and a 32 μm residue of 5.0 vol. % or less. By having the 4 μm residue of the coal ash be 40 vol. % or more, the content of fine coal ash particles can be reduced and the deterioration of the handleability can be suppressed. By having the 4 μm residue of the coal ash be 40 vol. % or more, the increase in the adiabatic temperature rise during hardening of the cement composition can be further suppressed, and the DEF suppression effect can be maintained for a longer period of time. By having the 32 μm residue of the coal ash be 20.0 volume % or less, the content of coarse particles in the coal ash is low, which suppresses a decrease in pozzolanic reactivity, suppresses a decrease in the strength of the hardened cement body (e.g., compressive strength, etc.), and further suppresses a decrease in the DEF suppression effect.

[0031] In this specification, the particle size of coal ash means a value determined by a laser diffraction particle size distribution analyzer. In this specification, the 4 μm residue of coal ash means the content ratio of particles having a particle diameter of 4 μm or more to the total amount of coal ash, and the 32 μm residue of coal ash means the content ratio of particles having a particle diameter of 32 μm or more to the total amount of coal ash.

[0032] The coal ash content is preferably high from the viewpoint of suppressing DEF, while being low from the viewpoint of improving the physical properties (e.g., compressive strength) of the hardened cement body. The coal ash content is 2.5 to 30.0 mass%, preferably 6.5 to 28.0 mass%, more preferably 7.0 to 23.0 mass%, still more preferably 7.5 to 20.0 mass%, and particularly preferably 8.0 to 18.0 mass%, based on 100 mass% of the total content of the cement clinker, the gypsum, and the admixture.

[0033] As the limestone, for example, powders mainly composed of calcium carbonate, such as limestone powder that is generally available on the market, and kansui stone powder, can be used. The limestone preferably includes those conforming to the minor mixing components described in JIS R 5210 "Portland cement".

[0034] The Blaine specific surface area of ​​limestone is preferably 2500 to 10000 cm 2 / g, and more preferably 4000 to 9000 cm 2 / g, and more preferably 6000 to 8000 cm 2 / g. The Blaine specific surface area of ​​limestone is 2500 cm 2 / g or more, the reactivity of the cement composition can be improved. 2 / g or less, deterioration of handleability can be suppressed.

[0035] The limestone content is preferably low from the viewpoint of suppressing DEF. 2From the viewpoint of low carbonization including reduction of generated amount, the higher the content, the more desirable. The content of limestone is 2.5 to 24.0 mass%, based on 100 mass% of the total content of the cement clinker, the gypsum, and the admixture, but is preferably 3.0 to 23.5 mass%, more preferably 7.5 to 23.0 mass%, further preferably 10.0 to 22.0 mass%, and particularly preferably 12.5 to 20.0 mass%. By having the content of limestone within the above range, heat generation accompanying hydration of the cement composition can be reduced, and the strength of the hardened cement body can be further improved. By having the content of limestone within the above range, the initial and long-term strength development of the hardened cement body can be further improved.

[0036] A mortar composition or a concrete-forming composition can be produced by adding, for example, fine aggregate, coarse aggregate, water and / or admixtures, and hardening accelerators to the above-mentioned cement composition. Mortar and concrete formed using the above-mentioned cement composition can exhibit excellent adiabatic temperature rise suppression, strength enhancement, and DEF suppression effects.

[0037] The fine aggregate may be one specified in JIS A 5005 "Crushed Stone and Crushed Sand for Concrete". Examples of fine aggregate include river sand, land sand, sea sand, crushed sand, silica sand, hard blast furnace slag fine aggregate, blast furnace slag fine aggregate, copper slag fine aggregate, and electric furnace oxidized slag fine aggregate. The fine aggregate may be used alone or in combination. The content of the fine aggregate in the above-mentioned cement composition may be, for example, 50 to 500 parts by mass with respect to 100 parts by mass of the total amount of the cement clinker, the gypsum, and the admixture.

[0038] The coarse aggregate may be one specified in JIS A 5005 "Crushed Stone and Crushed Sand for Concrete". Examples of the coarse aggregate include gravel, crushed stone, blast furnace slag coarse aggregate, and electric furnace oxidized slag coarse aggregate. One type of coarse aggregate may be used alone, or a combination of two or more types may be used. The content of the coarse aggregate in the above-mentioned cement composition is preferably 50 to 500 parts by mass relative to 100 parts by mass of the total amount of the cement clinker, the gypsum, and the admixture.

[0039] Examples of water include tap water, distilled water, and deionized water. The content of water in the above-mentioned cement composition is preferably 20 parts by mass or more and 60 parts by mass or less with respect to 100 parts by mass of the total amount of the above-mentioned cement clinker, the above-mentioned gypsum, and the above-mentioned admixture. By setting the content of water in the cement composition within the above-mentioned range, it is possible to sufficiently ensure the predetermined fresh properties (fluidity, air content, etc.) and moldability, and also to sufficiently suppress the decrease in the compressive strength and durability of the obtained cement hardened body.

[0040] Examples of the admixture include AE ​​agents, water reducing agents, AE water reducing agents, high performance water reducing agents, high performance AE water reducing agents, superplasticizers, antifoaming agents, shrinkage reducing agents, setting accelerators, setting retarders, and thickeners. Depending on the required performance, the admixture may be used alone or in combination. The content of the admixture in the above-mentioned cement composition is preferably 0.01 to 2 parts by mass with respect to 100 parts by mass of the total amount of the cement clinker, the gypsum, and the admixture.

[0041] Examples of hardening accelerators include potassium sulfate, sodium sulfate, lithium sulfate, anhydrous gypsum, quicklime, slaked lime, calcium nitrite, calcium nitrate, calcium chloride, alkali aluminate, alkali carbonate, triethanolamine, triisopropanolamine, methyldiethanolamine, diethanolisopropanolamine, calcium formate, maleic anhydride, calcium rhodanate, CSH nanoparticles, and calcium thiocyanate. The hardening accelerator may be used alone or in combination. The content of the hardening accelerator in the above-mentioned cement composition is preferably 0.1 to 20 parts by mass, more preferably 3.0 to 15 parts by mass, and even more preferably 6.0 to 10 parts by mass or less, relative to 100 parts by mass of the total amount of the cement clinker, the gypsum, and the admixture. By the content of the hardening accelerator being within the above-mentioned range, the hardening acceleration effect can be fully exhibited, and the promotion of setting and the decrease in fluidity can be suppressed.

[0042] The above-mentioned cement composition can be produced, for example, by the following method. One embodiment of the method for producing a cement composition is a method for producing a cement composition having a C calculated by the Bogue formula. 3 Cement clinker, gypsum, and blaine having a specific surface area of ​​3900 to 10000 cm 2 The method further comprises a step of mixing coal ash having a viscosity of 1.5 to 3.0 g with an admixture containing limestone (mixing step). In the above-mentioned manufacturing method, the cement clinker, gypsum, coal ash and limestone are mixed so that the coal ash content is 2.5 to 30.0 mass%, the limestone content is 2.5 to 24.0 mass%, and the admixture content is 5.0 to 32.5 mass%, assuming that the total content of the cement clinker, gypsum and admixture is 100 mass%.

[0043] The order of mixing the various components in the mixing step may be adjusted as appropriate. For example, cement clinker and gypsum may be mixed first, and then coal ash and limestone may be mixed, or cement clinker, gypsum, and coal ash may be mixed first, and then limestone may be mixed, or cement clinker, gypsum, coal ash, and limestone may be mixed at once. The mixing step may also serve as a crushing step for crushing the various components. For example, the above-mentioned production method may include a mixing step in which cement clinker, gypsum, and coal ash are fed into a crusher and mixed and crushed.

[0044] The mixing of the various components in the mixing step may be carried out using a mixer such as a pan mixer, a tilting mixer, or a ribbon mixer.

[0045] Although several embodiments have been described above, the present disclosure is not limited to the above-described embodiments. In addition, the descriptions of the above-described embodiments can be mutually applied. EXAMPLES

[0046] The present disclosure will be described in more detail below with reference to examples and comparative examples. However, the present disclosure is not limited to the following examples.

[0047] [Preparation of cement (mixture of cement clinker and gypsum)] The cements (NC1 to NC4) used in the examples and comparative examples described below are shown in Table 1. For all of the cements (NC1 to NC4), no admixture, which is a small amount of additive, was added, and gypsum dihydrate was first added to the cement clinker, which was then pulverized in a ball mill to prepare cement, which was a mixture of cement clinker and gypsum dihydrate.

[0048] Cement NC1 was prepared using C calculated by the Bogue formula. 3 Ordinary Portland cement clinker (manufactured by Ube Industries, Ltd.) with an A content of 10.2% was used. Cement NC2 was prepared using the C calculated by the Bogue formula. 3A test kiln-fired clinker with an A content of 15.8 mass% was used. Electric furnace-fired clinker was used to prepare cement NC3 and cement NC4.

[0049] Table 1 shows the Blaine specific surface area of ​​cement, its chemical components, and the mineral composition of the cement clinker used to prepare the cement (mineral composition of the clinker calculated using the Bogue formula). The Blaine specific surface area of ​​cement was calculated based on JIS R 5201:2015 "Physical testing methods for cement." The chemical composition of cement and the mineral composition of cement clinker were analyzed based on JIS R 5204 "Method for fluorescent X-ray analysis of cement." A Simultix12 manufactured by Rigaku Corporation was used for the fluorescent X-ray analysis.

[0050] [Table 1]

[0051] [Coal ash (fly ash)] Table 2 shows the coal ashes (FA1 to FA4) used in the examples and comparative examples described later. The coal ashes (FA1 to FA4) used were coal ashes collected from different thermal power plants. For FA3 and FA4, they were classified using a swirling airflow separator (Turbo Classifier, manufactured by Nisshin Engineering Inc.) at 3000 rpm to remove coarse particles, and the obtained fine fraction was further classified at 6000 rpm to remove very fine particles and adjust the particle size before use.

[0052] Table 2 shows the Blaine specific surface area and particle size of coal ash. The Blaine specific surface area of ​​coal ash was determined based on JIS R 5201:2015 "Physical Testing Methods for Cement". The particle size distribution of coal ash was measured by dispersing the coal ash in ethanol using a laser diffraction particle size distribution analyzer SALD2200 manufactured by Shimadzu Corporation.

[0053] [Table 2]

[0054] [Limestone] The limestone (CC) used in the examples and comparative examples described below was a 325 mesh product (passed through a 45 μm sieve) manufactured by Ube Material Industries, Ltd. The 325 mesh product had a Blaine specific surface area of ​​7470 cm 2 / g, calcium carbonate content is 90 mass% or more, and aluminum oxide content is 1.0 mass% or less, and it complies with JIS R 5210:2019 "Portland cement" minor mixed components.

[0055] [Fine aggregate] In the DEF test and activity index measurement, standard sand for cement strength testing from the Cement Association (Inc.) was used as fine aggregate. In the simplified adiabatic temperature rise test, crushed sand from Miyano, Yamaguchi Prefecture was used as fine aggregate.

[0056] (Examples 1 to 10 and Comparative Examples 1 to 9) Cement, coal ash, and limestone were mixed and pulverized in the mixing ratio (mass %) shown in Table 3 to prepare a cement composition.

[0057] [Table 3]

[0058] Using each of the cement compositions prepared in Examples 1 to 8 and Comparative Examples 1 to 8, a DEF test and activity index measurement were carried out.

[0059] [DEF test and activity index measurement] (Preparation of mortar composition) First, for each of the cement compositions prepared in the Examples and Comparative Examples, standard sand for cement strength testing by the Cement Association (a company) was mixed as fine aggregate, and water was mixed to prepare a mortar composition in accordance with the method described in JIS R 5201:2015 "Physical test method for cement". The composition of the mortar composition is shown in Table 4.

[0060] [Table 4]

[0061] (DEF Test) The DEF test is carried out by adding potassium sulfate as a hardening accelerator to the above-mentioned mortar composition and measuring the total SO 3 The amount of DEF was adjusted to 6% by mass, and pre-cured at a high temperature of 90°C to create conditions conducive to the formation of DEF. 3 If there is no increase in volume, there is a possibility that expansion due to DEF will not occur, and the above adjustment was made to make observation easier.

[0062] More specifically, the hardening accelerator was added to the mortar composition, and the mixture was mixed and molded. The mold was then sealed and placed in a thermostatic chamber, cured at 20°C for 4 hours, heated to 90°C for 2 hours, and held at 90°C for 12 hours. After 12 hours, the temperature was lowered to 20°C for 4 hours, and cured at 20°C for 2 hours. The mixture was then demolded to obtain a hardened mortar.

[0063] The mortar hardened bodies prepared by the above method were cured underwater in a thermostatic chamber at 20°C, and the length change of three hardened mortar bodies was measured for each level. The length change was measured using a dial gauge in accordance with the description of JIS A 1129-3:2010 "Method of measuring length change of mortar and concrete". The length change was measured by taking the mortar hardened bodies out of the water on the 7th, 14th, and 28th days after the age of underwater curing, and every 28 days thereafter, with the base length at the time of removal from the form as the time of removal. The length change was measured at six points on the front and back of the three hardened mortar bodies, and the average value was taken as the length change of the target hardened mortar body. The value obtained by dividing the length change by the interval (100 mm) of the strain gauge was taken as the expansion coefficient of the hardened mortar body, and the degree of expansion suppression of the hardened mortar body due to DEF was evaluated for the hardened mortar body 280 days after underwater curing according to the following criteria. The results are shown in Table 5. A: The expansion coefficient of the hardened mortar is 0.10% or less. B: The expansion coefficient of the hardened mortar is greater than 0.10% and less than 1.00%. C: The expansion rate of the hardened mortar exceeds 1.00%.

[0064] With regard to the degree of expansion inhibition, the hardened mortar of Comparative Example 1, which corresponds to normal Portland cement, was used as a standard, and if the expansion rate after 280 days of underwater curing was 1.0% or less by the same procedure, it was judged to have a sufficient expansion inhibition effect. Also, it was judged that a mortar composition that gives a hardened mortar with an expansion rate of 0.1% or less has an excellent expansion inhibition effect, and has an extremely high expansion inhibition effect.

[0065] (Activity index measurement) The compressive strength of each mortar hardened body was measured in accordance with the description of JIS R 5201:2015 "Physical Test Methods for Cement". The mortar hardened body for compressive strength measurement was prepared by first mixing the mortar compositions prepared according to the formulations in Tables 3 and 4 in a constant temperature room at 20°C as mortar, filling the formwork, and storing the formwork in a humidity box for 24 hours. After 24 hours of curing, the formwork was demolded to obtain a mortar hardened body. The obtained mortar hardened body was subjected to underwater curing in a constant temperature room at 20°C until the material age of 28 days, and then the compressive strength was measured. The activity index refers to the ratio of the compressive strength of the mortar hardened body to the compressive strength of the reference mortar hardened body, expressed as a percentage. The reference mortar hardened body was prepared in the same manner as the preparation of the mortar hardened body for the activity index measurement described above, using cement NC1 (ordinary Portland cement with no additives added), and the mortar hardened body was demolded at 20°C and underwater cured until the material age of 28 days. The compressive strength of the standard mortar hardened body was measured in the same manner, and the activity index of each mortar hardened body was calculated using the obtained value. Each mortar hardened body was evaluated according to the following criteria. The results are shown in Table 5. A: Activity index is 90% or higher. B: The activity index is less than 90%.

[0066] Regarding the evaluation of the activity index of the hardened mortar, if the activity index was higher than that of Comparative Example 6, in which only coal ash was added at 25%, that is, if the activity index was 90% or higher, it was judged to have sufficient compressive strength for practical use. In Comparative Example 6, the expansion of the hardened mortar in the DEF test was suppressed, but a decrease in the activity index was confirmed.

[0067] [Table 5]

[0068] In Table 5, "-" means that the measurement was not performed.

[0069] As shown in Table 5, in the compositions of Comparative Examples 1 and 3 to 5 in which limestone alone was used without coal ash as an admixture, it was confirmed that the effect of suppressing the expansion of the hardened mortar body in the DEF test could not be obtained even if the content of limestone was increased. In addition, from the results of the activity index measurement for the compositions of Comparative Examples 1 and 5, it was confirmed that the activity index also decreased. In contrast, the mortar compositions of Examples 1 to 8, which contain coal ash and limestone as admixtures in a predetermined ratio, were all confirmed to have an excellent effect of suppressing the expansion of the hardened mortar body in the DEF test. Similarly, it was confirmed that all of the mortar compositions of Examples 1 to 8 showed sufficient activity indexes and maintained sufficient compressive strength.

[0070] As shown in Table 5, it was confirmed that the mortar compositions of Examples 1 to 3, in which coal ash (FA1, FA3, or FA4) having a specified Blaine specific surface area was mixed in the same ratio as in Comparative Example 1, exhibited an excellent effect of suppressing the expansion of the hardened mortar body in the DEF test, compared to the composition of Comparative Example 2, in which coal ash (FA2) having a small Blaine specific surface area was used. Also, it was confirmed that the mortar compositions of Examples 4 to 7, in which the coal ash content was increased compared to the mortar compositions of Examples 1 to 3, exhibited an even more excellent effect of suppressing the expansion of the hardened mortar body in the DEF test.

[0071] As shown in Table 5, a comparison of the mortar compositions of Comparative Example 1 and Examples 3, 4, and 8, which contain the same proportion of limestone but different proportions of coal ash, confirmed that the effect of suppressing the expansion of the hardened mortar body in the DEF test improves as the coal ash content increases.

[0072] As shown in Table 5, a comparison between the composition of Comparative Example 6, which does not contain limestone, and the mortar composition of Example 8, which contains a specified amount of limestone, confirmed that a mortar composition with a superior activity index can be prepared by using coal ash and limestone in combination, and that the compressive strength can be improved. In addition, it was confirmed that the activity index of the composition of Comparative Example 7, which contains a large amount of admixture, is reduced, even in the case of a combination system of coal ash and limestone. Similarly, a comparison of the activity indexes of the mortar compositions of Examples 4 and 6 and the composition of Comparative Example 8 confirmed that when the limestone content and the admixture content are excessive, the effect of suppressing the expansion of the mortar hardened body in the DEF test is reduced, and the activity index is also reduced.

[0073] Using each of the cement compositions prepared in Examples 1, 7, 9, and 10 and Comparative Examples 1, 5 to 9, a simple adiabatic temperature rise test was carried out.

[0074] [Measurement of adiabatic temperature rise] (Preparation of mortar composition) First, crushed sand produced in Miyano, Yamaguchi Prefecture, as fine aggregate, and water were mixed with each of the cement compositions prepared in the Examples and Comparative Examples, and a mortar composition was prepared in accordance with the method described in JIS R 5201:2015 "Physical Test Methods for Cement". The composition of the mortar composition is shown in Table 6.

[0075] [Table 6]

[0076] (Simple adiabatic temperature rise test) A part of the mortar composition prepared as described above was subjected to a measurement of the adiabatic temperature rise. The adiabatic temperature rise was measured using an adiabatic calorimeter for small samples ATR-6L manufactured by Tokyo Riko Co., Ltd. More specifically, first, each material was weighed according to the mixing ratio in Table 6, the mortar composition was mixed by hand with a spatula, a certain amount was transferred to a measurement container, and a thermocouple was inserted. In this measurement, the temperature of the mortar composition was measured by a thermocouple, and the temperature in the tank around the mortar composition was controlled so that it was the same temperature as the measured temperature, thereby creating a state close to adiabatic conditions, and the obtained final temperature rise (°C) was regarded as the temperature rise in adiabatic conditions. However, although the device of the adiabatic calorimeter for small samples used in this test was close to adiabatic conditions, there was heat loss from the device, so the adiabatic temperature rise was calculated by compensating for the heat loss from the device in accordance with the method described in Non-Patent Document 3. Other measurement conditions and calculation details were performed in accordance with the description in Non-Patent Document 3. The final value of the adiabatic temperature rise (℃) plus the temperature of the mortar composition at the start of the measurement (20℃) was taken as the maximum temperature (℃) under adiabatic conditions (hereinafter referred to as the adiabatic maximum temperature), and was evaluated according to the following criteria. The results are shown in Table 7. A: The maximum insulation temperature is 68°C or less. B: The maximum adiabatic temperature is greater than 68°C.

[0077] Regarding the amount of adiabatic temperature rise, according to the JCI Guidelines for Prevention and Control of Cracks in Mass Concrete (Non-Patent Document 4), the limit value for the maximum concrete temperature is generally set at 70°C. Therefore, the above criteria were that if the adiabatic maximum temperature is 68°C or less, the decomposition of ettringite can be suppressed and the risk of DEF occurrence can be sufficiently reduced, and it was determined that there is a suppression effect.

[0078] [Table 7]

[0079] As shown in Table 7, a comparison between the mortar composition of Example 7 and the composition of Comparative Example 6, which have the same content of admixture, confirmed that the combined use of coal ash and limestone can suppress the increase in the adiabatic maximum temperature. 3 The composition of Comparative Example 9, which uses cement with different amounts of A, and the mortar compositions of Examples 9 and 10 were compared to determine the C of the cement clinker. 3 It was confirmed that as the amount of A decreases, the increase in the adiabatic maximum temperature can be further reduced, and it is expected that the decomposition of ettringite, which is the cause of DEF, can be further suppressed. [Industrial Applicability]

[0080] According to the present disclosure, CO 2 It is possible to provide a cement composition that can be produced with reduced emissions compared to conventional methods, that suppresses expansion associated with DEF, and that exhibits sufficient compressive strength development, as well as a production method thereof.

Claims

1. C calculated by the Bogue formula 3 Cement clinker having an A content of 9.5 to 14.0 mass%; Plaster and A mixture containing coal ash and limestone, The Blaine specific surface area of ​​the coal ash is 4100 to 10000 cm 2 / g, The total content of the cement clinker, the gypsum and the admixture is 100% by mass. The content of the admixture is 17.5 to 32.5 mass %, The coal ash content is 7.5 to 18.0 mass%, and The cement composition, wherein the limestone content is 10.0 to 22.0% by mass.

2. The content of the gypsum relative to the total content of the cement clinker, the gypsum, and the admixture is 100 mass %, and the content of the gypsum is SO 3 The cement composition according to claim 1, wherein the content is 0.5 to 3.5 mass%.

3. The cement clinker has a C calculated by the Bogue formula 3 The cement composition according to claim 1 or 2, wherein the S content is 35.0 to 65.0 mass%.

4. The cement composition according to any one of claims 1 to 3, wherein the coal ash has a 4 μm residue of 40 to 85 vol% and a 32 μm residue of 0 to 20.0 vol%.

5. Further containing a curing accelerator, The content of the hardening accelerator is 0.1 to 20 parts by mass with respect to 100 parts by mass of a total amount of the cement clinker, the gypsum and the admixture. The cement composition according to any one of claims 1 to 4.

6. C calculated by the Bogue formula 3 Cement clinker, gypsum, and plaster having an A content of 9.5 to 14.0 mass% and a Blaine specific surface area of ​​4100 to 10000 cm 2 / g of coal ash and a mixture containing limestone, In the step, the cement clinker, the gypsum, the coal ash, and the limestone are mixed so that the total content of the cement clinker, the gypsum, and the admixture is 100% by mass, the coal ash content is 7.5 to 18.0% by mass, the limestone content is 10.0 to 22.0% by mass, and the admixture content is 17.5 to 32.5% by mass.

Citation Information

Patent Citations

  • Sulfate and acid resistant concrete and mortar

    JP1998504511A

  • High fluidity mortar composition

    JP2012201532A

  • JP2016,2016,

  • High fluidity mortar composition

    JP2017065963A

  • Fly ash cement and fly ash cement composition

    JP2017154905A